Postoperative Noninvasive Ventilation Following Cardiothoracic Surgery: A Clinical Primer and Review of the Literature. (December 2015) - Gilliland, Samuel; Brainard, Jason
Postoperative pulmonary complications following cardiac and thoracic surgery are common and associated with significant morbidity and mortality. Noninvasive ventilation has emerged as a successful and well-validated strategy to treat various acute medical conditions. More recently, noninvasive ventilation has been studied in selective surgical patient populations with the goal of preventing postoperative complications and treating acute respiratory failure. In this clinical review, we will briefly examine the incidence of pulmonary complications following cardiothoracic surgery and the physiology and mechanics of acute respiratory failure and noninvasive ventilation. We then present a systematic review of the indications, patient selection, and current literature investigating the specific use of noninvasive ventilation in this population.